KAJIAN TENTANG PERANCANGAN TRACKING SYSTEM PEMANTAUAN PERGERAKKAN OBYEK MENGGUNAKAN LUCAS-KANADE - Randy Oetoroputra; Lina Lina; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
This application is developed for tracking object movements with Lucas-Kanade method.  The input data are of the positions of the targeted object and their RGB values. The process started by recording the position of the selected object. After an object is selected by the user, this application will start tracking  the object’s position. Kata Kunci : Tracking system, Lucas-Kanade, Jacobian matrix, greyscale, RGB.